Draft genome sequence of Mycobacterium bovis 04-303, a highly virulent strain from Argentina - Nishibe, Christiane (2013)
Mycobacterium bovis strain 04-303 was isolated from a wild boar living in a free-ranging field in Argentina. This work reports the draft genome sequence of this highly virulent strain and the genomic comparison of its major virulence-related genes with those of M. bovis strain AF2122/97 and Mycobacterium tuberculosis strain H37Rv.